Green teams: Understanding their roles in the environmental management of companies located in Brazil - Jabbour, Charbel José Chiappetta [UNESP]; Santos, Fernando César Almada; Fonseca, Sergio Azevedo [UNESP]; Nagano, Marcelo Seido (Elsevier, 2013)
Green teams are frequently considered in the state-of-the-art literature as an essential factor for companies aiming to implement and improve environmental management approaches and practices. However, most of the available literature on green teams is conceptual and theoretical by nature. Therefore, the main purpose of this article is to evaluate the main characteristics of green teams in Brazilian companies and to analyse the relationships between green teams and the maturity level of environmental management in those companies. Based on a conceptual background on corporate environmental management and green teams, a research was done in two complementary phases: a survey of 94 companies with ISO 14001 certification; and a multiple case study of four industrial companies. Survey results suggest that 82% of the studied companies have cross-functional green teams, i.e. involving various companies' departments; and 65% have functional green teams, i.e. individual department teams. The results of the case study suggest that the use of green teams is an instrument to the greening of companies with ISO 14001 in Brazil. The company with the most proactive and advanced environmental management is the same company which uses green teams more intensely. Green teams are especially necessary for implementing more technical environmental management practices, e.g. Life Cycle Assessment. Since this is one of the first studies analysing green teams, the results presented can be useful for companies and public policies aiming to implementation of environmental initiatives. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Brazil; Environmental management; Green teams; ISO 14001; Corporate environmental management; Environmental initiatives; Environmental management practices; ISO 14001 certification; Life Cycle Assessment (LCA); Life cycle; Research; Surveys; Industry